Genital Herpes in Human Immunodeficiency Virus Infected Patients - Stella Sunur; Izazi Hari Purwoko; Yulia Farida Yahya; Raden Pamudji (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Genital herpes is a recurrent, lifelong sexual transmitted infection caused by HSV, especially type 2. Genital herpes is the most common infection in HIV patient. HSV-2 can increase the risk of HIV acquisition 2 to 3 times. Clinical manifestations of genital herpes can be different between HIV- infected and non-HIV patients. HIV-infected patients have a high risk of developing chronic and severe genital ulcers with atypical manifestation, prolonged healing, and resistant to treatment, depends on CD4 count. Genital herpes can be diagnosed based on history, clinical manifestation, laboratory and histopathologic examination. Management of genital herpes includes education and counseling patients and sexual partners, systemic antiviral, and symptomatic treatment.